معيارالإسناد بين المحدثين والمؤرخين)الإمام الزهري كالنموذج(دراسة تحليلية - د. عبد الصمد شيخ; د. مسعود أحمد (Al Basirah, 2020)
The issue of isnad (chain of transmitters) is one of the big issues which have been discussed on a large scale between muslim historians and muhaditheen (traditionists). The problem actually lies in that the narratives of life of Prophet Muhammad PBUH divide into two major kinds. Some of them are related to his ritual and spiritual life which are called ahadith ul aqa’id wal ahkam. The other kind of narratives belongs to the general info about his life and character. The muhaditheen take care of ahdith ul aqa’id wal ahkam. On the contrary ،the historians are concerned for the other kind of narratives. The muhaditheen feel obliged when they narrate a holy prophet’s narrative to mention a complete isnad by ensuring certain conditions in its transmitters (ruwat) which are declared for them to be authentic. They try to strictly apply all rules from all aspects on every part of isnad. Contrariwise ،the historians do not bind themselves with the standards and principles set by muhaditheen. They see that the historical narratives are totally different from the nature of narratives of aqa’id and ahkam. They think that they can’t be over strict in the case of historical narrative; otherwise they will lose and miss a huge number of them ،and consequently ،they can’t explain the life of Prophet Muhammad (SAW )explicitly. In this article ،I have tried to express both points of view in this regard ، and to clarify to what extent we can apply muhaditheen’s rules regarding isnad over historical narratives to purify their strong from weak one. I have chosen Al-Waqidi as the model for this article because he is the most disputed figure in this regard. Most of criticism he faced from the muhaditheen’s critique was related to isnad’s issues.